The Use of Primer-Specific Targeting on Mitochondrial Cytochrome b Combined with Real-Time Polymerase Chain Reaction for the Analysis of Dog Meat in Meatballs - Henny Yulisa Manalu,; Sismindari,; Abdul Rohman, (Tropical Life Sciences Research, 2019)
The adulteration of beef with lower price meat such as dog meat is common to obtain an economic profit. Dog meat is non-halal for Islamic followers. This study was intended to design primer-specific targeting of the mitochondrial cytochrome b gene for the detection of DNA extracted from dog meat in meatball products. The results showed that Cyt b-55 could specifically amplify DNA from dog meat using an optimum annealing temperature of 57.9°C. Real-time polymerase chain reaction (PCR) using Cyt-55 primer could detect the presence of DNA at a concentration as low as 0.25 ng/mL, corresponding to 1% of dog meat in beef meatballs. The efficiency (E) values obtained were 91.2% and 110.8%for amplification using DNA extracted from fresh dog meat and dog meat in meatballs, respectively. The repeatability of the real-time PCR method was reliable, as indicated by the low value of relative standard deviation of cycle threshold (Ct) values from 6 replicates, namely, 0.91% (from DNA extracted from fresh meat) and 1.09% (from DNA extracted from meatballs). Real-time PCR using Cyt b-55 primer could be proposed as a standard method for the identification of dog meat in food products to ensure that they are halal and pure.